In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.
Publisher: University of Toronto Press

“We Paved the Way for Whatever Tolerance They Have in Their Lives”: An Interview with Michelle De Ville, “The First Door Bitch in Montreal” - Namaste, Viviane (Trans Activism in Canada: A Reader, 2014)
Centring the voices and experiences of trans identified people as experts on their own lives and agents of change, Trans Activism in Canada opens up a dialogue between scholars and community members in an effort to improve the lives of sex and gender variant people